2013
DOI: 10.1177/0734242x13507311
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of municipal solid waste treatment technologies from a life cycle perspective in China

Abstract: China has endured the increasing generation of municipal solid waste; hence, environmental analysis of current waste management systems is of crucial importance. This article presents a comprehensive life cycle assessment of three waste treatment technologies practiced in Hangzhou, China: landfill with and without energy recovery, and incineration with waste-to-energy. Adopting region-specific data, the study covers various environmental impacts, such as global warming, acidification, nutrient enrichment, phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 16 publications
0
36
0
Order By: Relevance
“…For example, China is considered as a country where the concept of a circular economy is obtaining an inreasingly important position, not only in research areas, but also at the political level [54]. Dong et al [55] studied the development of municipal solid waste in China based on used technologies. However, as the circular economy has been defined for advanced economies primarily, it would not be entirely valid for the rest of the world, which must endure the externalities of developed economies [36].…”
Section: Resultsmentioning
confidence: 99%
“…For example, China is considered as a country where the concept of a circular economy is obtaining an inreasingly important position, not only in research areas, but also at the political level [54]. Dong et al [55] studied the development of municipal solid waste in China based on used technologies. However, as the circular economy has been defined for advanced economies primarily, it would not be entirely valid for the rest of the world, which must endure the externalities of developed economies [36].…”
Section: Resultsmentioning
confidence: 99%
“…The total approximated amount of the released landfill gas is 125.6 m 3 per t-MSW. Methane accounts for 54.5% of the total gas (Dong et al, 2014a). The landfill gas in scenario 1 is emitted to atmosphere directly, whereas in scenario 2, 70% of landfill gas is collected and directed to a gas engine for electricity production with an efficiency of 39.1% (Dong et al, 2014a).…”
Section: Inventory Analysismentioning
confidence: 99%
“…The carbon content of different waste types is summarized in Table A.2SM and the DOC f is assumed to be 1. In Tianziling landfill, 54.5% volume of the landfill gas is CH 4 (CO 2 45%) and 65% of generated CH 4 is recovered and converted into electricity at an efficiency of 39.1% by a gas engine (Dong et al, 2014). A set of wastewater treatment equipment is installed and leachate is directly discharged to the city's sewage treatment system after purification.…”
Section: Tablementioning
confidence: 99%
“…Until now, LCA has been conducted in various waste management systems. Dong et al (2014) compared the incineration, landfill with and without energy recovery and concluded the incineration was more suitable for MSWM. Havukainen et al (2017) suggested that refuse derived fuel (RDF) production could improve the environmental impacts on waste incineration based on LCA results.…”
Section: Introductionmentioning
confidence: 99%